Peningkatan Motivasi Belajar Materi Iman Kristiani melalui Model Jigsaw di SMPN 8 Ngabang - Kristina Meni; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This Classroom Action Research was motivated by concerns over the competitive atmosphere that often characterizes conventional education systems. In many schools, students are conditioned to compete with one another from an early stage, reflecting the philosophy of "survival of the fittest" inspired by Darwin’s theory. Such an environment may foster individualism and reduce collaborative values among learners. To address this issue, a cooperative learning approach using the Jigsaw model was implemented in teaching Christian Faith material to Class IX students at SMP Negeri 8 Ngabang, Landak. The main objective was to enhance students' learning motivation and create a more engaging learning experience. The Jigsaw model, as a form of cooperative learning, encourages group collaboration, responsibility, and peer teaching, which helps students to develop a deeper understanding of the material and feel more involved in the learning process. The results of this study showed a noticeable improvement in students’ motivation, participation, and enjoyment during the learning process. The students were more active, attentive, and supportive of one another, creating a positive classroom atmosphere. This study concluded that the application of the Jigsaw model in teaching Christian Faith is effective in transforming a potentially monotonous subject into a dynamic and interactive experience. Therefore, cooperative learning methods, particularly the Jigsaw model, are recommended for broader use in religious education to foster not only academic achievement but also values of togetherness and mutual respect among students.